Variability of Lipids and Fatty Acids in Pacific Walrus Blubber - Jay, Chadwick V.; Iverson, Sara J.; Fischbach, Anthony S. (Frontiers in Marine Science, 2021)
The variability of lipid content and fatty acid (FA) composition across blubber depth and body sites are important considerations for condition and diet studies of marine mammals. We investigated lipid and FA variability among inner and outer blubber layers, three body sites, four study years, and lactation status of adult female Pacific walruses (Odobenus rosmarus divergens) using blubber samples collected from subsistence-harvested walruses in spring 2007-2010. Percent lipid content did not differ between the inner and outer blubber layers at the rump, flank, or sternum of walruses. Although FA composition differed between the inner and outer blubber layers, the difference was consistent across body sites, and differences between layers within individual FAs were small (< 2%). Lipid content at the sternum of lactating females was 6% higher than non-lactating females, consistent with known variation in body condition among these reproductive classes. Across study years, lipid content varied 18% and individual FAs varied 6%, likely reflecting population-level interannual variability in energy budgets and small differences in diet among years. Consistency in blubber lipid content across blubber depth and body sites and detectable variation in blubber lipid content among reproductive classes and years suggests the potential for lipid content to be a useful indicator of walrus body condition. In addition to information on condition, FA composition of blubber samples could potentially provide insights into changes in walrus diet that may be expected to occur from changes in their access to prey resources resulting from continued sea ice loss.